2017
DOI: 10.1111/cea.12976
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported signs of dampness at home may be a risk factor for chronic rhinosinusitis: A cross‐sectional study

Abstract: This study demonstrated an independent association between dampness at home and CRS in adults. The high burden of this and the other respiratory conditions studied is a strong argument in favour of countering indoor dampness by improving building standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…16 However, previous studies have shown associations between snoring and other respiratory conditions such as asthma and chronic rhinosinusitis. [31][32][33] Zhang et al 34 showed an association between building dampness and non-respiratory symptoms such as eye and skin symptoms, headache and fatigue. An association between indoor dampness and insomnia symptoms has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, previous studies have shown associations between snoring and other respiratory conditions such as asthma and chronic rhinosinusitis. [31][32][33] Zhang et al 34 showed an association between building dampness and non-respiratory symptoms such as eye and skin symptoms, headache and fatigue. An association between indoor dampness and insomnia symptoms has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…22 In addition, there were similar associations between dampness and chronic rhinosinusitis. In a study taken from the Swedish Galen study amongst 26 000 adults, these self-reported associations are again confirmed.…”
Section: Rhinitismentioning
confidence: 85%
“…In a study taken from the Swedish Galen study amongst 26 000 adults, these self-reported associations are again confirmed. 22 In addition, there were similar associations between dampness and chronic rhinosinusitis. Also, they reported some evidence for a dose-response relationship in terms of the number of positive dampness measures.…”
Section: Rhinitismentioning
confidence: 85%
“…Mady et al indicated that the exposure level of air pollutants significantly correlated with CRS symptom severity, particularly with a more pronounced impact on patients with CRSsNP ( 68 ). A cross-sectional study conducted in Sweden by Ahlroth Pind et al demonstrated an independent association between dampness at home and CRS in adults ( 69 ). Those findings are consistent with this study's results.…”
Section: Discussionmentioning
confidence: 99%